Sistem Penunjang Keputusan Berbasis Importance Performance Analysis Untuk Membantu Menentukan Peningkatan Fasilitas (Studi Kasus Fakultas Ilmu Komputer Universitas Bandadar Lampung) - . Julius; Ahm Cucus (Universitas Bandar Lampung (UBL), 2012)
University of Bandar Lampung in particular computer science faculty is the faculty that stood since 2000 and have two departments of technique informatics and information systems. FIK UBL always try to satisfy students, especially in providing facilities. Because the facility is one of the important priorities that must be Atfilled in order to satisfy students.In determining the facility is very difficult decisions in the analysis. Importance Performance Analysis has beengenerally accepted and used in various fields of study because of the ease to apply and display the results of analysis that facilitates performance improvement proposals.Importance Performance Analysis has the main function to display information related to service factors which greatly affect consumer satisfaction and their loyalty, and service factors that consumers need to be improved because according to current conditions have not been satisfactory.